2021
DOI: 10.1186/s43008-021-00061-3
|View full text |Cite
|
Sign up to set email alerts
|

Competing sexual-asexual generic names in Agaricomycotina (Basidiomycota) with recommendations for use

Abstract: With the change to one scientific name for fungal taxa, generic names typified by species with sexual or asexual morph types are being evaluated to determine which names represent the same genus and thus compete for use. In this paper generic names of the Agaricomycotina (Basidiomycota) were evaluated to determine synonymy based on their type. Forty-seven sets of sexually and asexually typified names were determined to be congeneric and recommendations are made for which generic name to use. In most cases the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 214 publications
(285 reference statements)
0
7
0
Order By: Relevance
“…Since a sequence of S. portentosum (type species, described from Pennsylvania) from Canada was distinct from the strongly supported sister lineage comprised of sequences of S. portentosum and S. hemidichophyticum from Europe, we suppose that all the European sequences represent S. hemidichophyticum and S. portentosum is restricted in distribution to North America. The two species, S. artocreas and S. incrustatum transferred from Michenera by Stalpers et al (2021) based on morphological evidence, were nested within the Scytinostroma s.s. Scytinostroma duriusculum is a cosmopolitan species and has been reported from many countries in subtropical and tropical areas ( Boidin and Lanquetin 1987 ; Bernicchia and Gorjón 2010 ). However, our phylogenetic analyses demonstrated that it could be a species complex, because three lineages were recognized from the samples of France, Sri Lanka, and China, Thailand and Vietnam.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Since a sequence of S. portentosum (type species, described from Pennsylvania) from Canada was distinct from the strongly supported sister lineage comprised of sequences of S. portentosum and S. hemidichophyticum from Europe, we suppose that all the European sequences represent S. hemidichophyticum and S. portentosum is restricted in distribution to North America. The two species, S. artocreas and S. incrustatum transferred from Michenera by Stalpers et al (2021) based on morphological evidence, were nested within the Scytinostroma s.s. Scytinostroma duriusculum is a cosmopolitan species and has been reported from many countries in subtropical and tropical areas ( Boidin and Lanquetin 1987 ; Bernicchia and Gorjón 2010 ). However, our phylogenetic analyses demonstrated that it could be a species complex, because three lineages were recognized from the samples of France, Sri Lanka, and China, Thailand and Vietnam.…”
Section: Discussionmentioning
confidence: 98%
“…& M.A. Curtis) Donk, is characterized by resupinate, effused basidiomes with a smooth to tuberculate hymenophore, a dimitic hyphal system with dextrinoid and cyanophilous skeletal hyphae, presence of gloeocystidia in most species, and subglobose to ellipsoid, variably amyloid or inamyloid, smooth basidiospores ( Bernicchia and Gorjón 2010 ; Liu et al 2018 ; Stalpers et al 2021 ). It is a widely distributed genus with 42 species level names in Index Fungorum ( http://www.indexfungorum.org , accessed on 1 January 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the recent taxonomic results (Wu et al 2020), the continuous use of the names Wolfiporia cocos and especially Poria cocos for the "Fuling" mushroom may cause uncertainty in scientific works and comparing its results. Therefore, in the present work, we recommend the acceptance and use of the taxonomically and nomenclaturally correct names Pachyma hoelen or Wolfiporia hoelen (Stalpers et al 2021). Furthermore, in the case of the applied research, we consider it expedient to identify the examined samples based on barcoding sequences and to compare them with the reference sequences of W. hoelen published by Wu et al (2020).…”
Section: Conclusion and Recommendationsmentioning
confidence: 95%
“…et al, have waxy, very small, and effused basidiomata different from the usually gelatinous, thick, orbicular basidiomata of Exidia , were recently transferred into Myxarium based on morphological and phylogenetic analyses (Spirin et al, 2018 ). Myxarium phylogenetically forms a monophyletic clade distantly related to Exidia and Tremellochaete (Spirin et al, 2019a ; Stalpers et al, 2021 ). In addition, Myxarium belongs to Hyaloriaceae, whereas Exidia and Tremellochaete belong to Auriculariaceae, and Myxarium can be distinguished from the latter two genera by its distinctly stalked basidia (Spirin et al, 2018 , 2019a ).…”
Section: Introductionmentioning
confidence: 99%